Drugs that offer the potential to reduce hospitalization and mortality from SARS-CoV-2 infection: The possible role of the sigma-1 receptor and autophagy. (3rd June 2021) - Brimson, James Michael; Prasanth, Mani Iyer; Malar, Dicson Sheeja; Brimson, Sirikalaya; Thitilertdecha, Premrutai; Tencomnao, Tewin
ABSTRACT: Introduction : Despite the availability of new vaccines for SARS-CoV-2, there has been slow uptake and problems with supply in some parts of the world. Hence, there is still a necessity for drugs that can prevent hospitalization of patients and reduce the strain on health care systems. Drugs with sigma affinity potentially provide protection against the most severe symptoms of SARS-COV-2 and could prevent mortality via interactions with the sigma-1 receptor. Areas covered : This review examines the role of the sigma-1 receptor and autophagy in SARS-CoV-2 infections and how they may be linked. The authors reveal how sigma ligands may reduce the symptoms, complications, and deaths resulting from SARS-CoV-2 and offer insights on those patient cohorts that may benefit most from these drugs. Expert opinion : Drugs with sigma affinity potentially offer protection against the most severe symptoms of SARS-CoV-2 via interactions with the sigma-1 receptor. Agonists of the sigma-1 receptor may provide protection of the mitochondria, activate mitophagy to remove damaged and leaking mitochondria, prevent ER stress, manage calcium ion transport, and induce autophagy to prevent cell death in response to infection.